Women's Work, Social Norms and the Marriage Market - Farzana Afridi; Abhishek Arora; Diva Dhar; Kanika Mahajan (Institute of Labor Economics (IZA), 2023)
While it is well-acknowledged that the gendered division of labor within marriage adversely affects women's allocation of time to market work, there is less evidence on how extant social norms can influence women's work choices pre-marriage. We conduct an experiment on an online marriage market platform that allows us to measure preferences of individuals in partner selection in India. We find that employed women are 14.5% less likely to receive interest from male suitors relative to women who are not working. In addition, women employed in 'masculine' occupations are 3.2% less likely to elicit interest from suitors relative to those in 'feminine' occupations. Our results highlight the strong effect of gender norms and patriarchy on marital preferences, especially for men hailing from higher castes and northern India, where communities have more traditional gender norms. These findings suggest that expectations regarding returns in the marriage market may influence women's labor market participation and the nature of market work.
Keywords: J12; J16; J24; 330; social norms; work choices; marriage market; gender; India